Energy-dense versus routine enteral nutrition in critically ill patients: a systematic review and meta-analysis - Zhang, Zonghong; Zhang, Chuanlai; Pan, Huiling; Yang, Ruiqi; Fang, Yin (Frontiers in Nutrition, 2025)
Background and aimCritically ill patients often experience low target attainment rates with enteral nutrition (EN), leading to malnutrition and poor clinical outcomes. Energy-dense EN may improve caloric delivery and reduce the risk of malnutrition. However, its effects on other clinical outcomes remain unclear. This systematic review aimed to evaluate the impact of energy-dense EN in critically ill patients.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, Cochrane Library, Clinical Trials, China Knowledge Network Infrastructure (CNKI), Wanfang Data, and Weipu databases from inception to December 2024. Two researchers independently screened studies and extracted data. Randomized controlled trials (RCTs) comparing energy-dense EN with routine EN in critically ill patients were included. Outcomes assessed included diarrhea, gastric residual volume (GRV), vomiting or reflux, mortality, total hospital length of stay (LOS), intensive care unit (ICU) LOS, duration of mechanical ventilation, and nutritional status. The risk of bias was assessed using the Cochrane RoB 2.0 tool. Meta-analyses were performed using Review Manager (RevMan), and the quality of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.ResultsA total of 380 studies were identified, and 10 RCTs comprising 4,473 patients were included. Compared with routine EN, energy-dense EN significantly reduced the duration of mechanical ventilation (MD = −37.41, 95% CI: −60.57 to −14.25, I2 = 75%) and ICU LOS (MD = −1.24, 95% CI: −1.49 to −0.99, I2 = 17%). Nutritional indicators such as albumin (MD = 4.92, 95% CI: 2.69–7.16, I2 = 89%) and prealbumin (MD = 55.97, 95% CI: 39.04–72.90, I2 = 86%) were significantly improved. However, there were no significant differences in total hospital LOS, mortality, or gastrointestinal complications such as diarrhea and vomiting/reflux. A slight increase in the risk of high GRV was observed (relative risk (RR) = 1.28, 95% CI: 1.19–1.37, I2 = 2%).ConclusionEnergy-dense EN appears to be safe and effective for critically ill patients, with benefits in nutritional status and reductions in ICU LOS and mechanical ventilation duration. However, this study has limitations, including potential bias in the included RCTs and inconsistent definitions of GRV. Future large-scale, high-quality, and multicenter RCTs with rigorous methodology are needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard.